Hydrological and climate intensification induces conservative behavior in the Hydrochorea corymbosa xylem production in a Central Amazon floodplain forest - de Sá, Priscila Amaral; Schöngart, Jochen; Wittmann, Florian; Piedade, Maria Teresa Fernandez; Tomazello-Filho, Mario; Oliveira, Rafael S.; Horna, Viviana; Parolin, Pia; Durgante, Flavia Machado (Frontiers in Ecology and Evolution, 2024)
Trees from flooded forests have to adjust their xylem hydraulic structure to face the annual flooding and the climatic conditions of the atmosphere. Usually, this adjustment of anatomical tissues in the tropics is driven by drought events inducing conservative behavior and can be recorded annually in tree rings. However, how the flood pulse and the climatic conditions influence the xylem hydraulic structure in floodplain trees is unknown. To fill this gap, we explore if flooded periods and monthly climate variation affect the annual tree growth and xylem anatomy structure for the tree species Hydrochorea corymbosa (Fabaceae) from the várzea flooded forest in the Central Amazon. We developed a 41-year ring width chronology ) and a 30-year time series of xylem anatomy parameters as mean hydraulic vessel diameter (Dh), vessel frequency (VF), and parenchyma quantity (PQ). We correlated the series with monthly hydrological and climatic data.The hydrological regime did not correlate with annual tree growth in that species as we previously expected but showed correlations with the xylem anatomical structure. High flood levels during the end of the flooding period induced conservative patterns of the anatomical structure, with a negative correlation with Dh (rho June=-0.40, p<0.05) and positive with the PQ (rho September/October= 0.42, p<0.05). These responses show that these trees are responding to flooding similar to the tree responses to drought. Regarding the climatic variation, the annual tree growth showed a negative correlation with the vapor pressure deficit (VPD), after the second half of the flooded period with the strongest correlation happening during the non-flooded period (rho December= -0.66, p<0. 01).These conservative patterns in tree behavior also happened when the maximum temperature negatively affected the vessel diameter (rho September=-0.42, p<0.05). In that case, we recognized two different moments that the environment is inducing conservative patterns in the xylem structure of those trees: 1-increasing the flood levels and; 2-the high evaporative demand during the nonflooded period. In this way, the intensification of the hydrological regime, as well as the strong drought conditions during the non-flooded periods, can be a risk for H. corymbosa in the Central Amazonian floodplains.